Bone Marrow Mesenchymal Stromal Cells: Identification, Classification, and Differentiation - Gao, Qianmin; Wang, Lipeng; Wang, Sicheng; Huang, Biaotong; Jing, Yingying; Su, Jiacan (Frontiers in Cell and Developmental Biology, 2022)
Bone marrow mesenchymal stromal cells (BMSCs), identified as pericytes comprising the hematopoietic niche, are a group of heterogeneous cells composed of multipotent stem cells, including osteochondral and adipocyte progenitors. Nevertheless, the identification and classification are still controversial, which limits their application. In recent years, by lineage tracing and single-cell sequencing, several new subgroups of BMSCs and their roles in normal physiological and pathological conditions have been clarified. Key regulators and mechanisms controlling the fate of BMSCs are being revealed. Cross-talk among subgroups of bone marrow mesenchymal cells has been demonstrated. In this review, we focus on recent advances in the identification and classification of BMSCs, which provides important implications for clinical applications.